Nurses' perception about the difficulties experienced in a High Complexity Oncology Center (Research, Society and Development, 2022)
Objective: To analyze nurses' perceptions about their routines and the challenges experienced in the daily care of people living with cancer. Methodology: Qualitative study with nurses who work in direct care for cancer patients at the High Complexity Center in Oncology, at the University Hospital Professor Alberto Antunes, conducted through semi-structured interviews, using Bardin's content analysis technique. Results: 14 professionals participated; after analysis, two categories emerged: “The nursing consultation as a qualifying instrument of care and the impact of the COVID-19 pandemic in a cancer center”; and “Difficult situations in the care of people living with cancer”. They identified multiple influencing factors of physical and psychological illness related to the daily routine of cancer care. Conclusion: The professionals presented influencing agents of physical and emotional exhaustion and made important reflections on the subject. It is pointed out that these professionals need preventive measures to assist in coping with everyday problems.